If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -24x + 14 + 35x = 53 Reorder the terms: 6 + 14 + -24x + 35x = 53 Combine like terms: 6 + 14 = 20 20 + -24x + 35x = 53 Combine like terms: -24x + 35x = 11x 20 + 11x = 53 Solving 20 + 11x = 53 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-20' to each side of the equation. 20 + -20 + 11x = 53 + -20 Combine like terms: 20 + -20 = 0 0 + 11x = 53 + -20 11x = 53 + -20 Combine like terms: 53 + -20 = 33 11x = 33 Divide each side by '11'. x = 3 Simplifying x = 3
| 10X^2-2X+8=0 | | 7x^2+57x+42=7 | | 6x-3x=15+4x | | 5x-1+3x=9 | | 6/7x2/5 | | a^2-13a=-12-6a | | 6a^2-13a+6a=-12 | | 2x+5-3x+1=0 | | 3/8*10x | | 4log(4x+5)=-2 | | 5x-1-3=2 | | 3b-4-3b/2 | | 9x+4=10x+3 | | Log[4](3X)=3 | | 8(4y)-9(y)+1=0 | | -25=2v-7 | | 7=-7(v+2) | | 5x+5+2x-2=-4 | | 64/8/2 | | (8d^5)/4d^-3 | | 38=3u-10 | | 2a=-(1-a) | | 10x+2=6x+42 | | 6X^3+60X^2+96X-160=0 | | -6x=24+18x | | 5w+9=54 | | 5x+1+2x-1=-4 | | 7(x+6)-9(9x-5)=15 | | 9(x+2)-2(x-8)=14 | | lnx=sqrt(8-lnx^2) | | -4n=-9 | | y=ln(x)+c |